The effect of marination on lactic acid bacteria communities in raw broiler fillet strips - Nieminen, Timo T.; Välitalo, Hanna; Säde, Elina; Paloranta, Anne; Koskinen, Kaisa; Björkroth, Johanna (Frontiers in Microbiology, 2012)
Marination with marinade containing salt, sugar and acetic acid is commonly used in Finland to enhance the value of raw broiler meat. In this study, the effect of marination and marinade components on composition and evolution of bacterial communities in modified atmosphere-packaged broiler fillet strips was investigated using culture-independent partial 16S rRNA gene sequencing and terminal restriction fragment length polymorphism. In unmarinated broiler fillet strips, Lactococcus spp. and Carnobacterium spp predominated at the early storage but were partially replaced by Lactobacillus spp. and Leuconostoc spp. when the chilled storage time was extended. In the marinated fillet strips, Lactobacillus spp. and Leuconostoc spp. predominated independent from the storage time. By mixing the different marinade components with broiler meat, we showed that marination changed the community composition and favored Leuconostoc spp. and Lactobacillus spp. by the combined effect of carbohydrates and acetic acid in the marinade. Marination increased the maximum level of lactic acid bacteria in broiler meat and enhanced CO2 production and acidification of meat during chilled storage. Accumulation of CO2 in the package head-space due to the enhanced growth of Leuconostoc spp. in marinated meat may lead to bulging of packages, which is a spoilage defect frequently associated with marinated and modified atmosphere-packaged raw broiler preparations in Finland.